O problema da consciência : abordagens em primeira e terceira pessoa - Lanoa, Liza Carolina Dabela (2022)
This dissertation aims to introduce a debate about phenomenal consciousness on contemporary philosophy. The main problem presented in this research is how difficult it is to explain phenomenal consciousness in physical terms or through materialistics approach. To materialism, phenomenal consciousness can be understood from an outside perspective, i.e., a third person perspective. However, authors like Thomas Nagel argue that the specificity of phenomenal consciousness can be perceived through a first person perspective. This becomes a philosophical problem because it takes away its subjective aspect to comprehend conscience through an objective approach. As a result of this discussion, this research aims to address conceptions about phenomenal consciousness as well as the impossibility to perceive it through a third person perspective. Thus, in the first chapter are presented concepts like acess consciousness, easy and difficult problem of conscience and the subjective character of experience. In the second chapter, a theory is presented that aims to study the conscience through a third person perspective. The chosen author for this debate is Daniel Dennet. From his ideas, I introduce his model of multiple draft and his critiques of cartesian theater. To conclude, I propose a discussion about the main theories tackled during the first and second chapters before their similarities and differences.